A Non-Violence Approach to Politics and Economics: Expanding the Principle of Nonviolence (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mahatma Gandhi is widely considered one of the most significant people in the history ofnonviolence. Practicing and practicing nonviolence in his daily life helped to make nonviolence ahousehold term. The most important finding in Gandhi's theory of action was Satyagraha, or Truthforce, which could be used by vast numbers of people in social and political protest. Satyagrahaallowed him to participate in collective action, which was both personal and social and political.Satyagraha was not driven by fear of retribution or pressure to fulfill one's obligations, including theright to reject collaboration with and support for a system that aims to improve the lives of individualsand society. Love is the foundation of Satyagraha, not hatred. In comparison to other modern pluralists,his worldview provides a more nuanced and realistic understanding of political philosophy and politicalpractice. Truth be told, nonviolence did not start with Gandhi. To the contrary, Mark Shepard has calledhim the father of nonviolence in reference to his nonviolent activity. Gandhi was the first in humanhistory to expand the principle of nonviolence from the individual to the social and political level.During the debate over an unidentified movement, Gandhi developed the word Satyagraha, whichincluded many comparable concepts.